Engineering procedures handbook - Cloud, Phillip A. (Noyes Publications, 1997)
Provides a systematic approach to engineering documentation for companies with small manual systems to those with mass production facilities.
Includes index.
Keywords: Engineering -- Management.; Engineering -- Documentation.; Technology -- Information services.; elektronické knihy; electronic books